2022
DOI: 10.1007/s00170-021-08576-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating fracture failure in origami-based sheet metal bending

Abstract: Origami-based sheet metal (OSM) bending is a promising new die-free folding technique for sheet metal. OSM bending principle is based on deforming the material along a pre-defined fold line, which is determined using material discontinuity (MD) produced by laser or waterjet cutting. The objective of this work is to study and evaluate the fracture in OSM bending under the influence of various MD types, kerfto-thickness (k/t) ratios, and sheet thicknesses. The research goal is to provide information on selecting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In general, the FLC is a good measure of failure caused by localized necking. However, under some particular process, for example hemming, hole expansion/ flanging, 17,18 Origami-based sheet metal (OSM) bending, 19 stretch-bending with small die radii, 20 incremental forming 21 etc., various failure types can occur, such as edge crack, 17 bending induced surface crack, 22 shear induced crack, 23 non-symmetric thinning 24 etc. It is often found that the local necking is suppressed and sheet metal can develop stable plastic deformation until fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the FLC is a good measure of failure caused by localized necking. However, under some particular process, for example hemming, hole expansion/ flanging, 17,18 Origami-based sheet metal (OSM) bending, 19 stretch-bending with small die radii, 20 incremental forming 21 etc., various failure types can occur, such as edge crack, 17 bending induced surface crack, 22 shear induced crack, 23 non-symmetric thinning 24 etc. It is often found that the local necking is suppressed and sheet metal can develop stable plastic deformation until fracture.…”
Section: Introductionmentioning
confidence: 99%